City and park: vizualization of meanings - V.S. Grytsenko (Ukrainian Cultural Studies, 2019)
The article is devoted to the interdependent identification of the city and park, which is carried out visualizing the opposition of their essential senses. In order to manage the traditional models of their consideration as separations, situationally constituent within the territorial union, the bases for examining the city as a space for the restoration of the human being and the need for its adequate, ontologically based, interdisciplinary studies, have been analysed. In this context, the park is considered as a visual legitimator of the city; the city is like the open dynamic structure that is in need of different, including indirect identificators. In such a way, a new – correlational – model of their study has been proposed, built on the visual ability to fix and covey the meanings.The visions of the city as the dominant territory of modern human implementation have real foundations resulting in the development of the relevant theoretical discourse, which is intended to find correct explanations. At this point, there is a connection of the city in its comprehensive value with the unified human being, which is the epicenter of the human matter realization – and in the processes of its permanent resurrection, and its own creativity as well. The force field of their attractive interaction foremost are man-made locations of the unutility nature, which represent the internal resource of decoding the humanistic symbolic signs.Absolute leaders in this essence are the parks designated in the city-building in the capacity of all recreational areas. In the visible picture of the city – its multivisuality – they have special words expressed by the way of visualization. Their use is optics directed to the depth of the human being. The park, built into the urban system, sharpens it as much as possible, facilitated by the controversy with the garden, in the visual text of which it fulfills a human saving function. Simultaneously, the park visions crystallize the semiosis of the city as a space of life-saving pragmatics.
Keywords: visualization of meanings, interdependent self-identification, multivisuality, sity vision, organic vision, areas of visual compromise